CLINICAL MASKS OF BONE SARCOMAS IN CHILDREN: SIX CLINICAL CASES - Maxim Yu. Rykov (Вопросы современной педиатрии)
Background. Solid tumors in children are one of the most common childhood malignancy, second only to hemoblastosis. Among solid tumours, about 5% are bone sarcomas: osteosarcoma (3%) and Ewing's sarcoma (2%). Atypicality of the these diseases course makes an early diagnosis a real challenge.Case Reports. The article presents six clinical observations of patients with bone sarcomas. We demonstrate the difficulties in diagnosing of this disease group which is associated with the absence of both specific symptoms and  distinct clinical picture.Conclusion. Pediatricians and pediatric surgeons should take into account the possibility of atypical course of bone sarcomas in children. Low cancer alertness is the reason for a significant delay in establishing the correct diagnosis which contributes to the tumour process generalization and reduces the chances of achieving remission while increasing the cost of treating such patients.